Menumbuhkembangkan Karakter Anak Panti Melalui Permainan Edukatif Studi Panti Asuhan Ulul Azmi Kota Cimahi - Eneng Martini; Jajang Hendar H; Lili Halimah; Purwanto Purwanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Character is very important to instill from an early age, because nowadays quite a few children grow up with global flows and intense use of gadgets. The implication of this is their character development in the future. In this program, the service activities we hold are given the theme